Air Stable, Photosensitive, Phase Pure Iron Pyrite Nanocrystal Thin Films for Photovoltaic Application - Bi, Yu; Yuan, Yongbo; Exstrom, Christopher L; Darveau, Scott A; Huang, Jinsong (Nano letters, 2011)
Iron pyrite (FeS2) is a naturally abundant and nontoxic photovoltaic material that can potentially make devices as efficient as silicon-based ones; however existing iron pyrite photovoltaic devices contain thermodynamically unstable FeS2 film surfaces that lead to low open circuit voltages. We report the rational synthesis of phase pure, highly crystalline cubic FeS2 nanocrystals (NCs) using a trioctylphosphine oxide (TOPO) assisted hot-injection method. The synthesized pyrite NC films have excellent air stability over one year. In contrast, obvious surface decomposition was observed on the surface of FeS2 NCs synthesized without TOPO. A high carrier mobility of 80 cm2/(V s) and a strong photoconductivity were observed for the first time for pyrite films at room temperature. Our results indicate that TOPO passivates both iron and sulfur atoms on FeS2 NC surfaces, efficiently inhibiting surface decomposition.